Influence of amorphous cellulose on mechanical, thermal, and hydrolytic degradation of poly(lactic acid) biocomposites - Wan Ishak, Wan Hafizi (Sci Rep, 2020)
Eco-friendly materials such as poly(lactic acid) (PLA) and cellulose are gaining considerable interest as suitable substitutes for petroleum-based plastics. Therefore, amorphous cellulose (AC) was fabricated as a new reinforcing material for PLA biocomposites by modifying a microcrystalline cellulose (MCC) structure via milling. In this study, the mechanical properties, thermal properties, and degradability of PLA were analysed to compare the effects of both MCC and AC on PLA. The tensile and impact properties improved at an optimum value with AC at 8 wt% and 4 wt% fibre loading, respectively. Notably, a scanning electron micrograph analysis revealed improved AC fibre–matrix adhesion, compared with MCC fibre–matrix adhesion, as well as excellent interaction between AC and PLA. Both MCC and AC improved the hydrolytic degradation of PLA. Moreover, the biocomposites with AC exhibited superior degradation when the incorporation of AC improved the water absorption efficiency of PLA. These findings can expand AC applications and improve sustainability.